New Method for Determination of Drain Saturation Voltage in Short Channel MOS Devices Between Liquid Helium to Room Temperature - Y. Amhouche; A. El Abbassi; K. Raïs; E. Bendada; R. Rmaily (Active and Passive Electronic Components)
A new method for drain saturation voltage extraction in submicron MOSFETs is presented. It is based on measurements of the partial derivative of the impact ionization rate. The method has been tested using main of channel length MOSFET devices and compared with others methods.